Comprehensive multi-omics analysis uncovers potential risks of aged sperm on offspring development after short-term storage - Yu Cheng; Songpei Zhang; Sayyed Mohammad Hadi Alavi; Rigolin Nayak; Swapnil Gorakh Waghmare; Nururshopa Eskander Shazada; Deepali Rahi Roy; Zhijun Ma; Otomar Linhart; Zuzana Linhartová (BMC Biology)
Abstract Background Recent studies have demonstrated that prolonged sperm storage adversely affects offspring through epigenetics, yet its broader effects on other molecular levels such as transcription and proteomics in progeny have been rarely explored. Results We employed comprehensive multi-omics approaches to uncover storage-induced epigenetic changes in sperm and their effects on embryonic development and offspring health. Sperm from common carp (Cyprinus carpio) was stored in vitro in artificial seminal plasma for 14 days, and the impacts of storage on functional properties of sperm and progeny development were investigated. We combined DNA methylome, transcriptomic and proteomic data to elucidate the potential mechanisms by which sperm storage influences progeny development. Prolonged in vitro storage significantly reduced sperm motility and fertilising ability which coincided with changes in the DNA methylation pattern. Integrated analyses of the offspring DNA methylome, comparative transcriptomics and cardiac performance measurements revealed storage-induced alterations of genes associated with nervous system development, myocardial morphogenesis and cellular responses to stimuli. Proteomic analyses showed that in addition to visual perception and nervous system function, pathways of the immunity system were also enriched. Results provide strong evidence of the epigenetic inheritance of the offspring’s performances when short-term stored sperm was used for fertilisation. Conclusions Short-term sperm storage induces heritable molecular and phenotypic changes in offspring, raising concerns over the potential intergenerational consequences of assisted reproductive practices in aquaculture and possibly other vertebrates.